Anti-oxidant and Aldose Reductase Inhibitory Activity of Piper betle Extracts: Biological Activity of Piper betle Extracts - Fatmawati, Sri; Shimizu, Kuniyoshi (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
Piper betle, known as daun sirih, is one of popular jamu ingredients which could be consumed freshly from the natural product resources by Indonesian people as traditional medicine. The present study is the primary article on human aldose reductase inhibition and also antioxidant activity of P. betle leaves extracts. The ethanol extract of P. betle exhibited the most inhibitory activity of the aldose reductase enzyme among extracts. It was discovered to present an IC50 value of 18.8 μg/mL for in vitro human aldose reductase and showed antioxidant activity by ORAC assay with value of 3861.2 ± 451.0 μmol Trolox Equivalent/g extract. Further investigation on the chemical components of the ethanol extract showed a total of 14 compounds by GC-MS analysis. The major compounds were bisphenol A (13) (34.4%) isoxylic acid (3) (13.8%), trans-phytol (11) (6.6%) and octadecyl aldehyde (14) (6.4%). These results implied that P. betle leaves should be prospective as an aldose reductase inhibitor.